2007
DOI: 10.1002/marc.200790032
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Rapid Commun. 16/2007

Abstract: Cover: A cationic water-soluble polyfluorene with excellent solubility and high PL quantum yield in water has been prepared. The high cationic density and appropriate side chain length of the polymer are the key factors to achieve such high water solubility. Further details can be found in the article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…(8). With 40 AE 0.2 L h À1 total fuel volume flow under ideal gas conditions, the H 2 S molar volume flow rates can be calculated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(8). With 40 AE 0.2 L h À1 total fuel volume flow under ideal gas conditions, the H 2 S molar volume flow rates can be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…With relatively high pH 2 S (in their case 20 ppm) further chemisorption of sulfur on nickel leads the oxidation of nickel at triple phase boundaries with oxygen ion flux from cathode and thus a further increase in anodic polarization and larger cell voltage loss. Wang et al [8] tested the cells with 2e50 ppm H 2 S with 50% H 2 /1.5%H 2 O/ 48.5%N 2 fuel. With 2 ppm H 2 S the initial cell voltage drop was 12.67% in 4 min.…”
Section: Introductionmentioning
confidence: 99%
“…Our early studies showed that only the quaternary ammonium system 1 was water soluble; corresponding primary amine, secondary N -methylamine, and tertiary N , N -dimethyl amines polymers were all surprisingly insoluble in aqueous media, even at reduced pHs. However, the quaternary salt 1 , very similar to a known material, 25 gave a clear solution in water even at neutral pH. Consequently we made a batch of this material via a modification of the literature procedure 25 that involved similar steps but in a different order (see ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain cationic polyfluorene homopolymers, the dioxaborolane monomer, 2,7-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-9,9 -bis [3-(N,N-dimethylamino) propyl]fluorene (39), was synthesized by reacting 38 with 2-isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxaborolane in the presence of n-BuLi (Scheme 1.19) [23]. The Suzuki polymerization between 38 and 39 and subsequent treatment with bromoethane led to the cationic homopolymer P54 with good water solubility.…”
Section: Cationic Poly(p-phenylene)smentioning
confidence: 99%